1996
DOI: 10.1007/bf00140592
|View full text |Cite
|
Sign up to set email alerts
|

Growth of five landlocked Arctic charr stocks under hatchery conditions

Abstract: Growth dynamics of five stocks of Arctic charr, were compared from the fry stage in June 1986 until December 1987. Each stock originated from a different lake in Sweden: Hornavan; Nfickten; Torr/Sn; Rensj6n and Visj6n. Hornavan charr reached the highest final mean weight (237 g), but they were not significantly heavier than VisjSn charr (206 g). Growth of fish of the three remaining stocks was similar but less rapid. The superior growth performance of Hornavan charr was most pronounced during autumn. Coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…LP2 charr were clearly the largest at the egg stage, but both SP and LP2 charr had grown to a corresponding body size during the first few months of exogenous feeding (by August). This is in line with the previous observations on different species of salmonids (Springate and Bromage 1985;Näslund and Henricson 1996;Heath et al 1999;Berrill and McCarthy 2008), indicating that the possible size advantage due to larger egg size disappears during early stages of growth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…LP2 charr were clearly the largest at the egg stage, but both SP and LP2 charr had grown to a corresponding body size during the first few months of exogenous feeding (by August). This is in line with the previous observations on different species of salmonids (Springate and Bromage 1985;Näslund and Henricson 1996;Heath et al 1999;Berrill and McCarthy 2008), indicating that the possible size advantage due to larger egg size disappears during early stages of growth.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to fish density, sexual maturation among 2+ fish needs to be considered as a potential factor affecting population-specific growths patterns. Although maturation is known to be accompanied by a slowing growth rate and an increasing size variation (Papst and Hopky 1983;Jobling et al 1993;Damsgård et al 1999), it seemed to have relatively limited effects on overall growth and size dispersion in our study (see also Näslund and Henricson 1996).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…1). In addition, in a later trial, the Hornavan predatory strain was found to have higher growth capacity than other strains of charr in Sweden (Näslund & Henriksson, 1996). For these reasons, in 1986, we choose the predatory morph from Lake Hornavan to be the starting population for a selective breeding programme.…”
Section: Evaluation Of Different Strainsmentioning
confidence: 98%